A Novel High Biosorbent of Pb-resistant Bacterium Isolate for the Removal of Hazardous Lead from Alkaline Soil and Water: Biosorption Isotherms In Vivo and Bioremediation Strategy. Issue 3 (16th March 2018) - Li, Xiaoping; Liu, Xianyu; Bao, Hongxiang; Wu, Ting; Zhao, Yanan; Liu, Dongying; Li, Xiaoyun; Yang, Tao; Yu, Hongtao
ABSTRACT: A novel Pb-resistant bacterium was isolated from aged lead-contaminated alkaline soils, and was identified as Bacillus megaterium via the MIDI protocol. The biosorption isotherms and kinetics of Pb(II) associated with B. megaterium in vivo in the alkaline environment were investigated at the first time. All the batch experiments of biosorption demonstrate that the B. megaterium uptake of lead is pH-dependent, exothermic (ΔH° = −5224.86 KJ mol −1 ), spontaneous, and fits well with the Langmuir isotherm, resulting in different kinetics under different examination temperatures. The maximum biosorption capacity is 503.86 mg g −1 at optimum conditions, which is much better in comparison to the biosorbent reported at the acidic condition in the literature. The Fourier-transform Infrared spectroscopic analysis of lead-loaded biomass confirms that the biosorption between B. megaterium and lead is the chemical adsorption in vivo . A site test indicates that B. megaterium really increases mobility and bioavailability of lead in Pb-contaminated alkaline soil in terms of chemical fractionation in vivo, which will potentially increase its uptake by hyperaccumulated plants in alkaline soils in arid or semi-arid areas of NW, China. Therefore, the novel isolate of B. megaterium with the highest adsorption capacity is a new promising biosorbent for the lead removal in alkaline water and soil. Graphic abstract: